Low-grade Papillary Schneiderian Carcinoma, a Unique and Deceptively Bland Malignant Neoplasm. (May 2015) - Lewis, James S.; Chernock, Rebecca D.; Haynes, Wesley; El-Mofty, Samir K.
<x xml:space="preserve">Abstract</x> The sinonasal tract harbors several different types of papillomas, some of which can progress to carcinoma. The most frequent among these are inverted and oncocytic Schneiderian papillomas. The rates of progression are somewhat controversial but are approximately 5% to 10% and are almost invariably described in the literature as in situ or invasive squamous cell carcinoma. Other carcinoma types, such as mucoepidermoid and sinonasal undifferentiated carcinoma, have also been described. Almost all of the described patterns of malignancy involve frank carcinoma with overtly dysplastic nuclear features, lack of cell maturation, and increased mitotic activity. Some squamous cell carcinomas, particularly nonkeratinizing, can grow in a papillary pattern, appearing to only line the surface epithelium, but they are cytologically overtly malignant throughout. In this case report, however, we describe a novel, human papillomavirus–negative, papillary carcinoma, which presented as a left nasal and maxillary sinus exophytic and inverted-appearing, papillomatous mass with very bland cytomorphology. The initial features were not typical for any defined Schneiderian papilloma but were also not clearly diagnostic of papillary carcinoma. The tumor recurred >10 times over 18 years despite extensive surgical resection including orbital exenteration. The tumor retained a bland appearance throughout the patient's entire clinical course, but did develop a pushing pattern of stromal invasion, increased mitotic activity, vesicular nuclei with prominent nucleoli, lymph node metastases, and eventually overwhelming local recurrence and nodal metastases, resulting in death. This tumor seems best characterized as a low-grade papillary Schneiderian carcinoma and appears to represent a novel type of sinonasal carcinoma.